Type 2 autoimmune pancreatitis associated with ulcerative colitis - Nan, Nan; Wang, Dongxu (Frontiers in Immunology, 2023)
Ulcerative colitis (UC) is a chronic idiopathic inflammatory disease mainly affecting the rectum and colon and causing diarrhoea and mucopurulent stools. UC can present with extraintestinal manifestations in various organs and systems and can be associated with various comorbidities. Autoimmune pancreatitis (AIP) is a specific type of pancreatitis associated with autoimmune abnormalities and is divided into two clinical types: type 1 (lymphoplasmacytic sclerosing pancreatitis) and type 2 (idiopathic ductocentric pancreatitis). The current study shows an association between type 2 AIP and UC, which may be related to genetic susceptibility, inflammatory factors, and immune response. The most common manifestation of AIP in patients with type 2 AIP–UC is abdominal pain with elevated pancreatic enzymes, whereas the presentation of UC in type 2 AIP–UC is more severe, with an increased risk of UC-related surgery. This review focuses on diagnosis, prevalence, pathogenesis, impact, and treatment to better understand type 2 AIP–UC, explore the molecular mechanisms of this condition, and encourage further research into the management of type 2 AIP–UC.